GOVERNMENT DEBT VS. CONSUMPTION: TESTING RICARDIAN EQUIVALENCE IN SIX ASEAN COUNTRIES - Fathoni, Nur Qoyyim; Hakim, Lukman (Journal of Applied Economics in Developing Countries, 2022)
Fiscal policy in the form of government debt becomes an exciting debate using the Ricardian Equivalence Hypothesis. Because the Ricardian Equivalence Hypothesis is opposite to Keynes's theory, the Ricardian Equivalence Hypothesis assumes that the community behaves rationally; government debt at this time will lead to a public burden in the future, and government debt will not affect society's consumption. This study examines the validity of the Ricardian Equivalence Hypothesis in six ASEAN countries using secondary data on household consumption, government debt, gross domestic product (GDP), government expenditure, and tax revenue. The study uses a data panel model in the period following the Asian crisis in 1998 and the period following the global crisis in 2008. The aftermath of the Asian crisis showed a variable of government debt, gross domestic product, and government expenditure with a significant overpost on household consumption. In contrast, the tax revenue variable negatively affected household consumption. The results estimation of the global post-crisis estimate es indicate gross domestic product variable with significant overage on household consumption while the government debt variable, government expenditure, and tax revenue have a negative relationship to household consumption.